Studi Korelasi Pengembangan Destinasi Wisata Alam Kebun Raya Samarinda Dengan Konservasi Lingkungan - Rini Koen Iswandari; Rinto Dwiatmojo; Eman Sukmana; Sabalius Uhai (Samarinda State Polytechnic, 2019)
Research Objectives to find out how the relationship between the development of tourist destinations and environmental conservation in Samarinda Botanical Garden, the results of the study show that there is a very positive relationship and strong relationship between developments in terms of infrastructure, infrastructure carried out with environmental conservation for the progress tourism and for the preservation of the environment around the Samarinda Botanical Garden Nature Tourism destination, which shows a positive and strong number between the independent variables (X), namely development with the dependent variable (Y) environmental conservation. Then the relationship between development and environmental conservation is smaller which shows there is significance.